Kinerja dan Profesionalisme Pegawai sebagai Kunci Kepuasaan Nasabah Bank Syariah Indonesia - Firdayetti, Firdayetti; Rahma, Syakila Kania (Bukhori: Kajian Ekonomi dan Keuangan Islam, 2025)
Purpose: This study aims to identify the relationship between employee performance and professionalism and the level of customer satisfaction at Bank Syariah Indonesia (BSI), especially in the West Jakarta area. Research Methodology:  This type of research is quantitative using a correlational approach. Data collection techniques included questionnaires and data analysis tools using smartphones. Data analysis techniques include outer model tests consisting of convergent validity, descriptive validity, and internal consistency reliability, whereas inner model tests consist of determination coefficients, predictive relevance, goodness of fit, and hypothesis testing. The number of respondents in this research is 160 respondents. Results: Employee performance and professionalism have a significant positive influence on customer satisfaction. Professionalism has proven to have a more dominant influence than employee performance. Conclusion: Employee performance and professionalism significantly and positively affect customer satisfaction at Bank Syariah Indonesia, West Jakarta. Limitation: This study is limited to the West Jakarta area and only uses secondary data of 160 respondents consisting of 35 customers of KCP Jakarta Cengkareng, 8 customers of KCP Duri Kosambi, 6 customers of KCP Jakarta Joglo, 9 customers of KCP Jakarta Kalideres, 8 customers of KCP Jakarta Kedoya, 7 customers of KCP Jakarta Kelapa Dua, 8 customers of KCP Jakarta Kemanggisan, so the results may not fully reflect conditions in other areas or include other relevant variables in the Islamic banking industry. Contribution: This study provides a practical contribution by highlighting the importance of improving employee competency and compliance with professional standards to improve customer satisfaction. Academically, this study adds to the literature on the influence of human resources on service quality in the Islamic banking sector.